2011
DOI: 10.1093/carcin/bgq286
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-wide aneuploidy study (CWAS) in workers exposed to an established leukemogen, benzene

Abstract: Evidence suggests that de novo, therapy-related and benzene-induced acute myeloid leukemias (AML) occur via similar cytogenetic and genetic pathways, several of which involve aneuploidy, the loss or gain of chromosomes. Aneuploidy of specific chromosomes has been detected in benzene-related leukemia patients as well as in healthy benzene-exposed workers, suggesting that aneuploidy precedes and may be a potential mechanism underlying benzene-induced leukemia. Here, we analyzed the peripheral blood lymphocytes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 47 publications
1
58
1
1
Order By: Relevance
“…Zhang et al (2011) has reported dose-dependent chromosomal aneuploidies (monosomy & trisomy) in the peripheral blood lymphocytes of 47 workers exposed to benzene . In another study published by Zhang et al (2012) an increased monosomy 7 and 8 level was found in 28 benzene-exposed workers in comparison to control subjects .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Zhang et al (2011) has reported dose-dependent chromosomal aneuploidies (monosomy & trisomy) in the peripheral blood lymphocytes of 47 workers exposed to benzene . In another study published by Zhang et al (2012) an increased monosomy 7 and 8 level was found in 28 benzene-exposed workers in comparison to control subjects .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Alguns estudos relacionaram a trissomia do cromossomo 21 a um estágio de "pré-leucemia", tendo visto que pacientes com este câncer têm alta incidên-cia dessa alteração em nível celular [62][63][64] . Euploidia é o fenômeno onde uma célula apresenta um valor múltiplo do número de cromossomos haplóides (n).…”
Section: Teste De Aberrações Cromossômicasunclassified
“…It is also very useful for examining most specific chromosomal rearrangements related to human leukemia and lymphoma in populations exposed to potential leukemogens and lymphomagens and for studying the aneuploidy-inducing effects of chemicals in a chromosome-wide manner. Our previous CWAS study using this technique demonstrated that certain chromosomes may be more affected than others by exposure to benzene 8,10 , a primary industrial chemical and a ubiquitous environmental pollutant that causes human leukemia 14 . This phenomenon of "selective aneuploidy" could be explored in other chemical exposures using CWAS.…”
Section: Hybridizationmentioning
confidence: 99%
“…We have applied this new Chromosomic approach in a CWAS study of benzene-exposed Chinese workers 8,10 .…”
Section: Introductionmentioning
confidence: 99%